Study of Some Biomarkers and HLA-G for Early Detection of Multiple Sclerosis Disease - Khamael Abdulla Taha; Mayada N. Iqbal; Gheyath Abd Ali Shalal (Institute of Medico-legal Publications Pvt Ltd, 2021)
Multiple sclerosis is the most commonest a chronic inflammatory, demyelinating and neurodegenerativedisorder in the central nervous system (CNS) of the brain and spinal cord. The disease commonly start onsetin the age of (20-50)years, as for women, they are at greater risk of MS than men. The aim of this dissertationis to detected some biomarkers(IL-18, Caspase-1 and Opioid growth factor) in the serum and saliva inpatients with MS and study the HLA-G genotype. Moreover, the current study indicated a comparisonbetween the levels of biomarkers in two groups for MS patients (early diagnosis of MS without treatmentand with treatment group) with the group of healthy controls. This study included the total number 150case, it was classified to the group I early diagnosis without treatment (54 patients) , the group II usingtreatment (46 patients)and the group III (50) healthy controls. This study included its own questionnairestructural, where it includes the following: gender and age. Biomarkers were examined by ELISA methodsand (HLA-G) it was done by PCR,PCR Sequencing methods. The age mean +SD of the untreated groupof new early diagnosis of MS was recorded (35.54 ± 8.51) and the treated group MS (34.22 ± 8.24) while(36.5 ± 8.93) in normal population controls. This study showed the concentrations(IL-18, Caspase-1 andOGF) in the serum and saliva of MS patients for both groups comparison healthy controls. This study wasconducted using a ROC chart for patients with MS in Iraq for biomarkers for both groups. In the currentstudy investigated the effect of HLA-G 14bp polymorphism on MS. As well as, to genotype (+ 3142G>